Performance analysis for complex embedded applications. (27th January 2006) - Jersak, Marek; Richter, Kai; Ernst, Rolf
Most existing performance analysis techniques for multi-processor systems with dynamic scheduling assume simple task dependencies. In realistic system, task dependencies are often complex, including multirate data dependencies, multiple activating inputs and cyclic dependencies or conditional communication. In this paper, we focus on the calculation of activation timing in the presence of such dependencies. These calculations have been integrated into a system-level performance analysis framework for heterogeneous architectures. Using a larger example, we demonstrate the use of this novel performance analysis for verifying all timing constraints, and for rapid design-space exploration and system optimisation.